Colour Words (Hand-Made Visualisations of Literature): A Maker’s Reflection - Thompson, Karen M. (Art/Research International, 2023)
In her making practice, Colour Words, Thompson represents the words used to describe colour in novels as embroidered squares on paper. In doing so, she creates alternate visualisations of literature, which has led to more questions, discoveries of patterns, and a new way of thinking about and relating to narratives and text/s. In this article, Thompson describes her making practice/process as an example of small data methodology and reflects on the experience to draw out meaning.